Complex coacervation of anthocyanin-rich pigments from red cabbage (Brassica oleracea) with inulin, gum arabic and pea protein - Muñoz-Coyotecatl, Sandra; Domínguez-Uscanga, Astrid; Ortiz-Castro, Randy; Rosas-Saito, Greta H.; Romero-De la Vega, Gregorio; Amador-Espejo, Genaro; Luna-Vital, Diego A. (Frontiers in Nutrition, 2025)
Complex coacervation is a widely used method for bioactive compound microencapsulation. Red cabbage extract is a natural pigment that contains anthocyanins, which provide attractive and bright colors with no reported toxicity and associated healthy properties. These types of pigments have led to a deep interest in developing natural colorants to at least partially replace their synthetic counterparts in the food industry. The present study aimed to encapsulate red cabbage extract using a complex coacervation system comprising gum arabic:inulin (GA:In) and pea protein (PP) as wall materials. A total of four treatments were tested, maintaining a consistent pea protein concentration (1%), and the concentrations of GA:In (1 and 3%) and red cabbage extract (1 and 10%) were varied. The results showed high encapsulation efficiency values, with all treatments achieving encapsulation levels above 95%. The total monomeric anthocyanin concentration was 6.7 μg anthocyanin Eq. C3G/mg of flour, and to explore bioactivity of the extract, α-amylase inhibition was analyzed, with an inhibitory percentage of 22.48% at a concentration of 0.5 mg/mL. The solubility of the coacervates ranged from 70.12 to 75.84% in water, and their morphology revealed irregular and porous shapes. Fourier Transform Infrared Spectroscopy (FTIR) analysis confirmed the formation of the coacervate-encapsulation complex. Characteristic bands showed the presence of functional groups from the wall materials and the encapsulated anthocyanins. These findings showed that the use of GA, In and PP as wall materials in complex coacervation can develop natural colorants with improved stability and functionality.